GERAKAN LITERASI SEKOLAH MELALUI PROGRAM POJOK BACA - Erviyenni, Erviyenni; Hajar, Siti; Safitri, Welinda (STKIP Pesisir Selatan, 2022)
This study aims to see the school literacy movement through the reading corner program at SMA Negeri 1 Kuantan Mudik, Bukit Pedusunan Village, Kuantan Mudik District, Kuantan Singingi Regency. This research includes descriptive research. The time of this research starts from September 8, 2021 to November 5, 2021. The data collection technique in this study uses observation, interviews and documentation. The results showed that the benefits of the reading corner were broadening students' horizons, adding to the vocabulary collection, training students to be creative, and being able to foster students' reading enthusiasm.